Overview of Prognosis of FLT3 Mutations and Interactions with Other Genetic Alterations in Acute Myeloid Leukemia - Ayşe Gül Bayrak Tokaç; Aynur Dağlar Aday (Sakarya Tıp Dergisi)
Acute Myeloid Leukemia (AML) is one of the most aggressive hematological malignancies. It has a highly heterogeneous genetic background and complex clonal evolution. In this letter, we emphasized the prognostic importance of a crucial biomarker in acute myeloid leukemia (AML) – the Fms - like tyrosine kinase 3 (FLT3), a receptor tyrosine kinase that plays a significant role in several cellular signalling processes. FLT3 is found on hematopoietic stem cells and early progenitor cells. After binding to its ligand, activated FLT3 triggers intracellular kinase, leads to cellular proliferation, and inhibits differentiation and apoptosis.